Pengaruh Skeptisisme Sistem Pengelolaan Arsip Unit Dalam Negeri dan Kliring pada PT Bank Syariah Indonesia KC S. Parman - Maulana Iskandar; Ahmad Amin Dalimunthe2 (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study examines the records the executives framework for inside and clearing units at PT. Bank Syariah Indonesia KC S. Parman. The motivation behind this paper is (1) to portray how the inside and clearing unit document the board framework at PT. Bank Syariah Indonesia Kc S. Parman(2) depicts the limitations looked during the time spent recording the inside and clearing the board unit at PT. Bank Syariah Indonesia Kc S. Parman(3) portrays the endeavors made to defeat obstructions in the recording system of the Homegrown and Clearing the executives unit at PT. Bank Syariah Indonesia KC S. Parman. Information was gathered through perception, meetings, and writing study. interviews with the top of the inside and clearing unit, the boss of the inside unit and the clearing and general staff at PT. Bank Syariah Indonesia Kc S. Parman Broke down the information graphically. Keywords: the executives; documents; Clearing Unit